Development of submicromolar 17β-HSD10 inhibitors and their in vitro and in vivo evaluation - Benek, Ondrej; Vaskova, Michaela; Miskerikova, Marketa; Schmidt, Monika; Andrys, Rudolf; Rotterova, Aneta; Skarka, Adam; Hatlapatkova, Jana; Karasova, Jana Zdarova; Medvecky, Matej; Hroch, Lukas; Vinklarova, Lucie; et al. (European journal of medicinal chemistry, 2023)
17β-hydroxysteroid dehydrogenase type 10 (17β-HSD10) is a multifunctional mitochondrial enzyme and putative drug target for the treatment of various pathologies including Alzheimer's disease or some types of hormone-dependent cancer. In this study, a series of new benzothiazolylurea-based inhibitors were developed based on the structure-activity relationship (SAR) study of previously published compounds and predictions of their physico-chemical properties. This led to the identification of several submicromolar inhibitors (IC50 ∼0.3 μM), the most potent compounds within the benzothiazolylurea class known to date. The positive interaction with 17β-HSD10 was further confirmed by differential scanning fluorimetry and the best molecules were found to be cell penetrable. In addition, the best compounds weren't found to have additional effects for mitochondrial off-targets and cytotoxic or neurotoxic effects. The two most potent inhibitors 9 and 11 were selected for in vivo pharmacokinetic study after intravenous and peroral administration. Although the pharmacokinetic results were not fully conclusive, it seemed that compound 9 was bioavailable after peroral administration and could penetrate into the brain (brain-plasma ratio 0.56).
Keywords: vztahy mezi strukturou a aktivitou; Alzheimerova nemoc; 17-hydroxysteroidní dehydrogenasy; Enzyme Inhibitors; Structure-Activity Relationship; 17-Hydroxysteroid Dehydrogenases; lidé; Brain; Alzheimer Disease; inhibitory enzymů; mozek; Humans